Vstup firmy Thermal Trend s.r.o. na rumunský trh - Pěnčíková, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce se zabývá vývozem českých výrobků na rumunský trh. Autorka navrhuje na základě analýzy firmy a zvoleného teritoria vhodný způsob vývozu koupelnových radiátorů firmy Thermal Trend, s.r.o. na rumunský trh, s cílem rozšířit odbytiště výrobků této firmy.

This diploma thesis focuses on export of Czech products to Romanian market. The author proposes a suitable way of exporting bathroom radiators produced by company Thermal Trend, s.r.o. to Romanian market, with the aim of expanding company’s operations sales.
Entry to the Romanian Market by Company Thermal Trend, s.r.o.
Keywords: Mezinárodní obchod; rizika v mezinárodním obchodě; PEST analýza; SWOT analýza; analýza konkurence; International Business; Risks of International Busiess; PEST analysis; SWOT analysis; Competition analysis